Feasibility of integrating calcium and iron–folate supplementation to prevent preeclampsia and anemia in pregnancy in primary healthcare facilities in Kenya. Issue Volume 14:Issue S1(2018) (1st March 2018) - Omotayo, Moshood O.; Dickin, Katherine L.; Pelletier, David L.; Martin, Stephanie L.; Kung'u, Jacqueline K.; Stoltzfus, Rebecca J.
Abstract: Calcium (Ca) supplementation to prevent preeclampsia can save maternal and newborn lives, but there are no program models for integration into existing antenatal care platforms. We used a program impact pathway model to guide the design of integrated Ca and iron–folate (IFA) supplementation in Kenya. We provided healthcare providers with job aids (posters and counseling cards), trained them on counseling techniques and supplementation guidelines, and developed behavior change materials for pregnant women (pill‐taking calendars). We allocated health facilities to prescribe either 1.0 or 1.5 g/day Ca, with standard IFA. We collected implementation data from 16 facilities and 990 women. We also explored effects of supplementation on percentage of the population meeting recommended daily allowance. Supplements and job aids were available during 90% of facility spot‐check episodes; calendar availability was lower (78%). Over 98% of clients received Ca and IFA supplements, but only 76% received enough Ca supplements to last between antenatal care visits. Among clients that still had pills by return date, adherence was 77% and 83% for the IFA and Ca regimen, respectively. When 1.5 g/day of Ca supplements were prescribed, over 75% of participants met recommended daily allowance. Only 54% met the recommended daily allowance when 1.0 g was prescribed. This study illustrates a systematic approach for integrating Ca supplementation into primary healthcare and demonstrates that such integration is feasible when contextual bottlenecks are addressed. Policy makers and program planners should pay attention to supply chain, healthcare worker dispensing behavior, and appropriateness of regimen for their settings.